L’historien face au conflit : Homs et la révolte - Vanessa Guéno (Revue des Mondes Musulmans et de la Méditerranée)
Until 2011, when the revolutionary sparkle was lit in Homs (Syria), it was a place considered being insignificant or forgotten by most people. Its revolutionary effervescence transformed the city – until then without any major historical events – to an emblematic city and the apocalyptic images of the events were accessed/used by the media and by the local stakeholders thanks to social media. In this context, facing these brutal actions, the role and position of the historian needs to be reconsidered. It forces him/her to review his/her understanding of the past, of his/her choice of source material and their interpretation of them. With the transformation of the field of study into a “battlefield”, the concept of tangible and intangible heritage is renewed. Be it abandoned old stones, disused local expressions or forgotten popular rituals, the people of Homs are rediscovering their city and reclaim their heritage. In this chaos, can the historian continue to dissociate/distance from the events and the emotions. Does the history of Ottoman Homs written in 2007 need to be rewritten?